Perbaikan Metode Kerja Untuk Meningkatkan Produktivitas Karyawan pada Bengkel Bubut Saudara Teknik ANO - Wankrisman Hia; Abdul Azis Syarif; Farida Ariani Daulay (CV. IRA PUBLISHING, 2023)
In this study, we analyzed the existing work processes in the lathe workshop. We identified the main problems affecting employee productivity and designed suitable solutions to improve their performance. This study aims to determine work methods for increasing employee productivity at the Lathe Workshop. The research was conducted at the Saudara Teknik ANO Lathe Workshop in Medan City, North Sumatra Province, and used the rapid entire body assessment (REBA) method. The results of calculating the %CVL for each employee obtained a value of <30%, which means that fatigue does not occur. And the results of calculations with the REBA method have a score between 4 to 7 which states that it has a moderate level of risk and needs corrective action. It is expected that improving this work method will provide significant benefits in increasing employee productivity in the lathe workshop. By implementing the proposed solutions, it is hoped that the efficiency and effectiveness of work processes can be increased, production time can be reduced, and the resulting product quality will be increased.